2020
DOI: 10.1242/dev.186338
|View full text |Cite
|
Sign up to set email alerts
|

The Rho guanine nucleotide exchange factor Trio is required for neural crest cell migration and interacts with Dishevelled

Abstract: Directional migration during embryogenesis and tumor progression faces the challenge that numerous external signals need to converge to precisely control cell movement. The Rho guanine exchange factor (GEF) Trio is especially well suited to relay signals, as it features distinct catalytic domains to activate Rho GTPases. Here, we show that Trio is required for Xenopus cranial neural crest (NC) cell migration and cartilage formation. Trio cell-autonomously controls protrusion formation of NC cells and Trio morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…Thus, the extracellular domain may also be required for Wnt/receptor complex formation and possibly Dvl recruitment, which leads to local activation of RhoGTPases and is involved in CIL downstream signaling. In this context, Ptk7-mediated Dvl recruitment may also support Cadherin-11/Trio signaling, as we have recently shown that the GEF2 domain of Trio interacts with the DEP domain of Dvl [37]. Like Ptk7, Cadherin-11 is required for CIL in NC cells [30].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Thus, the extracellular domain may also be required for Wnt/receptor complex formation and possibly Dvl recruitment, which leads to local activation of RhoGTPases and is involved in CIL downstream signaling. In this context, Ptk7-mediated Dvl recruitment may also support Cadherin-11/Trio signaling, as we have recently shown that the GEF2 domain of Trio interacts with the DEP domain of Dvl [37]. Like Ptk7, Cadherin-11 is required for CIL in NC cells [30].…”
Section: Discussionmentioning
confidence: 93%
“…Like Ptk7, Cadherin-11 is required for CIL in NC cells [30]. Cadherin-11 interacts with the RhoGEF Trio, which can activate RhoGTPases [37,38]. As Trio was also shown to be important for microtubule catastrophe at the cell-cell contact site [39], this module may provide multiple ways to relay information from the cell-cell contact site to the cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a growing body of data in animal models proves the interplay between RHO and Wnt during embryonic NC migration (reviewed by Mayor and Theveneau, 2013). In this context, Kratzer et al (2020) have recently provided evidence for a novel and a complex modulatory mechanism acting during frog development, where Rho GEF Trio activates Rac1 at the level of cell protrusions of migratory cranial NC via interaction with Dvl, a major player of PCP signaling (Gao and Chen, 2010), similar to other Dvl-dependent mechanisms seen for Rho activation in Xenopus, Drosophila, and zebrafish development (Schlessinger et al, 2009). It is also becoming clear that RAC1 is involved in a positive regulation of canonical Wnt signaling by enabling the nuclear accumulation of β-catenin (Wu et al, 2008;Schlessinger et al, 2009).…”
Section: Pcp and Wnt Signalingmentioning
confidence: 99%
“…As in mice, Dvl function is also required for neural tube closure by regulating CE movements of the midline and coordinating polarity among epithelial cells (Wallingford and Harland, 2002;Seo et al, 2017). In addition, Dvl2-mediated activation of Rac1 through the DEP domain also controls the protrusive activity of neural crest cells during migration (Kratzer et al, 2020). Because cellular polarization is tightly dependent on the asymmetric activation of Wnt/PCP signaling, both reduced and increased levels of Dvl disrupts asymmetric movements.…”
Section: Distinct and Redundant Dvl Functions During Xenopus Developmentmentioning
confidence: 99%